LITERATURE REVIEW : Pengaruh Aquatic Plyometric Training Terhadap VO2Max Pada Pemain Basket - Asti Safitria (2020)
Basketball players need maximum oxygen capacity to maintain physical fitness in physical activity that is long enough. VO2Max is an important factor for players to reach the peak of optimal performance. Aims: The writing of this literature review aims to examine the literature, journals, articles or results of previous studies on the topic of the influence of aquatic plyometric training on VO2Max in basketball players. Methods: Research search in the form of literature review by collecting several data sources, using electronic data sourced from Google Schoolar. The research sample used 3 articles selected according to specified criteria. Quality assessment methodology in this study uses the Scimago Journal & Country Rank (SJR) and The Level Of Internal Validity value with a minimum category B according to the Critical Appraisal of Studies. Analysis of the 3 journals was based on the suitability of the topic and the research method used. Result: After a review of literature as many as 3 articles show that aquatic plyometrics can improve one's VO2Max. Conclusion: Aquatic plyometric training can significantly increase VO2Max in basketball players.